The outcome of the surgical treatment in the patients with the penetrating chest wounds - Šego, Krunoslav; Dulić, Grgur; Ugljen, Ranko; Lekšan, Igor; Ivanović, Marko, liječnik; Šimundić, Tihana; Ištvanić, Tomislav (2009)
Abstract: The aim of this paper is to present the treatment evaluation of the chest penetrating wounds in our hospital during the Patriotic war in Croatia. Due to the war situation, all the patients were treated with the aggressive surgery - thoracotomy. We compared the treatment outcome of these patients with those treated after the war who were treated with the standard procedure, meaning that the thoracotomy was performed only if the indications were clear and most of the minor chest wounds were treated with the thoracic drain. The compared parameters were: age, gender, thoracotomy percentage in comparison to total number of wounded, incidence of multiple wounds needing surgery, total follow-up period, infection incidence, period of hospital treatment, blood transfusions, spirometry finding minimum one year after the hospital treatment. None of the parameters showed any significant statistical difference suggesting that one treatment was better than the other.
Bibliografija
Sažetak
Keywords: Prsni koš -- Ozljede prsnog koša -- Kirurški zahvat -- Torakotomija -- Hospitalizacija -- Ishod liječenja -- Domovinski rat; Hrvatska